Splenic metastasis from recurrent chromophobe renal cell carcinoma 12 years post-nephrectomy: A case report (2021)
Background: Renal cell carcinoma (RCC) metastases to the spleen are rare. At the time of this report, only 20 cases of splenic metastases from RCC have been published in the literature. To our knowledge, this report represents the first case of splenic metastasis from a chromophobe RCC. Case presentation: A 44-year-old woman presented with clinical and radiological features of splenic metastasis from RCC, 12 years after radical nephrectomy for chromophobe RCC. Computed tomography, laparotomy, and splenectomy revealed metastases to the spleen and retroperitoneal lymph nodes. Conclusion: Splenic metastasis from RCC is uncommon, and even rarer from a chromophobe subtype of RCC. Surgical management of the metastasis is recommended.